The Differences between NAD-ME and NADP-ME Subtypes of C4 Photosynthesis: More than Decarboxylating Enzymes - Rao, Xiaolan; Dixon, Richard A. (Frontiers in Plant Science, 2016)
As an adaptation to changing climatic conditions that caused high rates of photorespiration, C4 plants have evolved to display higher photosynthetic efficiency than C3 plants under elevated temperature, high light intensities and drought. The C4 plants independently evolved more than 60 times in 19 families of angiosperms to establish similar but not uniform C4 mechanisms to concentrate CO2 around the carboxylating enzyme Rubisco. C4 photosynthesis is divided into at least two basic biochemical subtypes based on the primary decarboxylating enzymes, NAD-dependent malic enzyme (NAD-ME) and NADP-dependent malic enzyme (NADP-ME). The multiple polygenetic origins of these subtypes raise questions about the association of C4 variation between biochemical subtypes and diverse lineages. This review addresses the differences in evolutionary scenario, leaf anatomy, and especially C4 metabolic flow, C4 transporters and cell-specific function deduced from recently reported cell-specific transcriptomic, proteomic and metabolic analyses of NAD-ME and NADP-ME subtypes. Current omic analysis has revealed the extent to which component abundances differ between the two biochemical subtypes, leading to a better understanding of C4 photosynthetic mechanisms in NAD-ME and NADP-ME subtypes.